The Influence of Creatine Use on Performance of Swimmers - Hakan Acar; Erkut Tutkun; Osman İmamoğlu; Tülin Atan (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the effects of creatine use on the performance of swimmers. The existing literature was reviewed. The studies were presented in tables. It was found that most of the studies on creatine use in swimming branch were on single sprint performance, repeated interval swimming set performance and increase in strength. Increases were found in maximal swimming time and recovery capacity. 1,52% performance increase was found in sprint swims. Increases between 2-8% were found in total work performance. There were also studies which did not report any effect of creatine on performance. One of the reasons why such studies did not report any effects is insufficient creatine loading. In swimmers who use creatine, the effects are generally seen in fat-free body weight, total body weight and amount of body water. In controlled studies conducted on swimmers, both plasma concentration increase and elevation of total creatine amount in muscles can occur with creatine supplement intake (daily about 20 gr). This increase can be positively reflected in performance. It can contribute to swimmers’ aerobic and anaerobic endurance of upper and lower extremities, sprint running and sprint swim speed, maximal strength and strength continuity and recovery speed in-between repeats and post-training. Its use should be conducted in normal doses under physician control.